ANALISIS PERBANDINGAN METODE SMART DAN AHP PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TELADAN DI SMK REVANY JAMBI: Analytic Hierarchy Process;Exemplary Teachers;AHP Method;SMART Method;Teacher Selection;Simple Multi Attribute Rating Technique;Decision Support System. - Kahar, Novhirtamely; Puad, Lailyn; Vanessya , Thania (JURNAL AKADEMIKA, 2021)
Giving appreciation for the high achievements and dedication achieved by teachers in carrying out their professional duties needs to be given, one of which is the selection of exemplary teachers. The selection of exemplary teachers should be able to motivate teachers to improve performance, discipline, dedication, and loyalty for the future interests of the nation and state. The current implementation of the selection of exemplary teachers is only based on personal observations from the assessors, namely based on certain criteria. To reduce errors in the assessment, it can be assisted with a decision support system that can assist the assessor in determining the selection of exemplary teachers. The methods used in this research are SMART (Simple Multi Attribute Rating Technique) and AHP (Analytical Hierarchy Process). Inputs to this system are user data, question input data, criteria data, and alternative data. The criteria used in the study were Principal Assessment, Teacher Assessment, and Student Assessment. The output of this system is a report on the results of the overall calculation of the results of the SMART and AHP methods, and a report on the results of the comparison of the SMART and AHP methods. The final result of the study shows exemplary teachers based on criteria and alternatives calculated by the two AHP and SMART methods and the results of the selection are shown by the highest number of calculations from each prospective exemplary teacher. The comparison results from the sensitivity analysis of the AHP method are better recommended.